The Role of Technology-Based Audits (Digital Audits) in Improving Audit Quality in Accounting Firms Public in the Industrial Era 4.0 - Dian Pitra Amalia; Nurwahyuni; Indira Hasbah; Muchriana Muchran (IECON: International Economics and Business Conference, 2025)
The development of digital technology has brought about major changes in audit practices, especially in the Industry 4.0 era. This study aims to analyze the role of digital audit in improving audit quality in Public Accounting Firms (KAP). With a causal quantitative approach, data were collected through closed questionnaires to auditors in the Makassar area. The results show that the implementation of digital audit and the effectiveness of the audit process have a positive and significant effect on audit quality. Technologies such as CAATs, big data analytics, and artificial intelligence enable auditors to work faster, more accurately, and more objectively. This study provides a practical contribution to KAP in optimizing digital transformation strategies, and emphasizes the importance of training and infrastructure in the successful implementation of audit technology.